Erythropoietic protoporphyria: case reports for clinical and therapeutic hints - Cristina Tumminelli; Francesca Burlo; Serena Pastore; Giovanni Maria Severini; Irene Berti; Stefano Marchini; Davide Zanon; Eleonora De Martino; Alberto Tommasini (BMC, 2023)
Abstract Background Erythropoietic protoporphyria is a rare disorder which represents an important health problem in children, causing painful photosensitivity. Little is known on the correlation between genetic profile and clinical manifestations. The standard of care for Erythropoietic protoporphyria is based on avoiding sun and using sun protections, but recent literature has suggested that cimetidine may have a role in improving sun sensitivity. Herein we report our case series describing the successful use of cimetidine and analyzing potential phenotype-genotype correlations. Case presentation This case series describes five patients presented to our Rheumatology Service complaining sun sensitivity. Blood exams and genetic analysis were consistent with the diagnosis of erythropoietic protoporphyria. Four of 5 patients received cimetidine in addition to standard therapies and the effect of treatment was evaluated by Erythropoietic Protoporphyria - Quality of Life questionnaire. Conclusions Erythropoietic protoporphyria usually manifests in early childhood after a short sun exposure. Skin manifestations are the main reason for investigations, although sometimes they can be more subtle, leading to a significant diagnostic delay. Skin diseases in children can have profound effects on their family and social relationships. A treatment with cimetidine appears to be an excellent therapeutic option in children with Erythropoietic protoporphyria.